Does Speculative News Hurt Productivity? Evidence from Takeover Rumors - Christian Andres; Dmitry Bazhutov; Douglas Cumming; Gerrit Köchling; Peter Limbach (University of Cologne, Centre for Financial Research (CFR), 2024)
We show that productivity at both the firm and employee (i.e., analyst and inventor) level temporarily declines upon announcements of takeover rumors that do not materialize. Such speculative news may hurt productivity because uncertainty and threat of job loss cause anxiety, distraction, and reduced commitment among employees and managers. Consistently, we observe a more pronounced productivity dip for rumored targets and when the likelihood of job loss is higher. Firm performance mirrors these results. We find no indication of reverse causality. The evidence fosters our understanding of potential real effects of speculative financial news and the costs of takeover threats.
Keywords: D24; G00; G34; J24; 330; Employee commitment and distraction; Employee and firm productivity; Firm performance; Takeover speculation; Threat of job loss